Evaluation of Spoke Type IPM Synchronous Motors for IE4 Efficiency Class - Ustun, O.; Kara, D. Bayram (IEEE, 2018)
In this paper, the assessment of a line-start spoke type rotor IPMSM (interior permanent magnet synchronous motor) design for super premium efficiency class (IE4) is discussed. Due to the hybrid rotor structure, these motors have three torque components: reluctance, PM and cage (induction) torques. Cage torque characteristics determine the motor's starting and synchronization capabilities while the reluctance and the PM torques form steady-state behavior. The design study shows that spoke type rotor structure can carry these features properly. A 2.2 kW, 4-pole, general purpose, line-start, spoke type IPMSM is arranged satisfying the requirements of IE4 efficiency class. And also, the addressed design is compared to the other line-start IPMSM types, in terms of performance parameters, ease of manufacturing, cost and synchronization capabilities.